High frequency of WNT-activated medulloblastomas with CTNNB1 wild type suggests a higher proportion of hereditary cases in a Latin-Iberian population - Moreno, Daniel Antunes; Bonatelli, Murilo; Antoniazzi, Augusto Perazzolo; de Paula, Flávia Escremim; Leal, Leticia Ferro; Garcia, Felipe Antônio de Oliveira; de Paula, André Escremim; Teixeira, Gustavo Ramos; Santana, Iara Viana Vidigal; Saggioro, Fabiano; Neder, Luciano; Valera, Elvis Terci; et al. (Frontiers in Oncology, 2023)
Purpose Medulloblastomas are the most common primary malignant brain tumors in children. They are divided into molecular subgroups: WNT-activated, SHH-Activated, TP53 mutant or wild type, and non-WNT/non-SHH (Groups 3 and 4). WNT-activated medulloblastomas are usually caused by mutations in the CTNNB1 gene (85%–90%), and most remaining cases of CTNNB1 wild type are thought to be caused by germline mutations in APC. So far, the frequencies of CTNNB1 have been reported mainly in North American and European populations. The aim of this study was to report the frequency of CTNNB1 mutations in WNT-activated medulloblastomas in a Latin-Iberian population and correlate with their clinicopathological characteristics. Methods A total of 266 medulloblastomas from seven different institutions from Brazil (n=211), Portugal (n=38), and Argentina (n=17) were evaluated. Following RNA and DNA isolation from formalin-fixed, paraffin-embedded (FFPE) tumor tissues, the molecular classification and CTNNB1 mutation analysis were performed by nCounter and Sanger sequencing, respectively. Results WNT-activated medulloblastomas accounted for 15% (40/266) of the series. We observed that 73% of WNT-activated medulloblastomas harbored CTNNB1 mutations. CTNNB1 wild-type cases (27%) were more prevalent in female individuals and suggested to be associated with a worse outcome. Among the CTNNB1 wild-type cases, the available analysis of family history revealed two cases with familiar adenomatous polyposis, harboring APC germline variants. Conclusion We observed a lower incidence of CTNNB1 mutations in WNT-activated medulloblastomas in our Latin-Iberian cohort compared to frequencies previously described in other populations. Considering that CTNNB1 wild-type cases may exhibit APC germline mutations, our study suggests a higher incidence (~30%) of hereditary WNT-activated medulloblastomas in the Latin-Iberian population.